153 Dose monitoring in synchrotron radiation breast computed tomography with radiochromic films. (December 2018) - Masi, M.; Di Lillo, F.; Mettivier, G.; Sarno, A.; Arfelli, F.; Brombal, L.; Donato, S.; Fedon, C.; Rigon, L.; Russo, P.
Abstract : Purpose: To measure the dose distribution in a phantom during a synchrotron radiation (SR) computed tomography (CT) scan using radiochromic films, for procedure assessment and for offline dose monitoring in SR breast CT. Methods: We used XR-QA2 radiochromic films (calibrated in terms of free air kerma) and a 14-cm PMMA cylindrical phantom. Measurements were performed at the SYRMEP beamline of ELETTRA facility, within the SYRMA-3D project for phase-contrast breast CT[1] . The phantom was positioned at isocenter, pending from the patient bed. Measurements were performed at 38 keV, beam size of 3 mm  × 150 mm (H × W), at an air kerma corresponding to a mean glandular dose of 5 mGy in a 14-cm diameter 50% glandular breast. The phantom was irradiated over 360° first with a film at the mid-plane, and then with film strips wrapped on its surface. Additional tests were made over 180° with an axial scan pitch of 1, 0.8 or 0.5. Results: Results show a dose map at mid-plane the phantom, indicating the cup-shaped horizontal profile due to primary and scatter dose. Analogous maps were recorded with the films at the periphery of the phantom, representing the surface dose maps. Conclusions: We performed measurements of the dose distribution in a phantom during a SR CT scan with different irradiation geometries. This technique produces evidence for selecting the suitable scan procedure. Moreover, as an offline monitor system, a piece of calibrated radiochromic film wrapped on a suitable holder around the breast could record the history of the organ irradiation.